Investing in perennial pastures - A real options approach - Tozer, Peter; Stokes, J. (Wiley, 2009)
In investment analysis, uncertainty and irreversibility can undermine net present value(NPV) as a decision rule since the option to delay investment may have value. We applythe real option theory of investment to the pasture investment decision facing livestockproducers in southwestWestern Australia. In 2006, livestock producers thinned their herdsas pasture availability dwindled due to extreme drought conditions. This left producerswith a unique opportunity to either establish new perennial pastures for their cattle orutilize volunteer annual pasture and invest in more sheep breeders. In either case, largeand irreversible investments fraught with multiple sources of uncertainty implies that onecan gain useful insights by casting the investment problem in a real option context. Theresults suggest that required rates of return for each investment alternative are about 1% to 1.5% higher than standard NPV would suggest with sheep production having the lower required rate of return.